Analisis Faktor-Faktor yang Memengaruhi Kinerja Guru pada SMA Swasta di Kota Batam - Leonardo, Leonardo; Muchsinati, Evi Silvana (Jurnal Manajemen Bisnis dan Keuangan, 2024)
This study aims to explore the correlation between organizational learning, work motivation, and work discipline on teacher performance with job satisfaction as a mediator. Data were collected through a questionnaire from 194 teachers at private schools in Batam City and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that organizational learning, motivation, and work discipline influence teachers' job satisfaction, while motivation and work discipline positively affect teacher performance. Organizational learning does not directly impact teacher performance. Job satisfaction does not serve as a significant mediator between the independent variables and teacher performance, as the influence of job satisfaction on performance may be affected by other more dominant factors, such as specific aspects of the work environment and individual conditions not measured in this study.